Penyelenggaraan Jaminan Hari Tua Terhadap Asisten Rumah Tangga Yang Bekerja Pada Orang Perseorangan Pasca Diberlakukannya Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Gusminarti, Gusminarti; Fithrina, Hendria (Nagari Law Review, 2023)
To achieve the government's goal of providing decent work for the community as accommodated in the Constitution Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia as regulated through a derivative regulation of Law Number 13 of 2003 which regulates Manpower. The presence of this arrangement provides certainty to the workforce who are people who can do work to produce goods and services both to meet their own needs and for the community. However, over time, there were several changes to the regulations with the presence of the Job Creation Act which reduced the labor guarantee. In this regard, the author will examine several problems, namely: how is the protection of old-age insurance in the social security system for workers in Indonesia, how is the application of the rules for the protection of old-age insurance to the participation of household assistants who work for individual employers, what appears in providing this old-age insurance protection for household assistants, and what efforts will be made by the Manpower Office in embracing household assistants to become participants in the old-age insurance protection. With the presence of several problems that will be studied by the author using a normative juridical research method that will focus on labor legislation, this is also strengthened by a qualitative approach method. The presence of an effort to protect the workforce by providing Old-Age Security protection, especially to Household Assistants, is the answer that we want to produce for efforts with the presence of regulations that protect ART in Indonesia